PENGARUH SELF EFFICACY DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA KARYAWAN PIE SUSU CHANDRA - Kadek Yushanta Nugraha; I Wayan Sujana; Ni Nyoman Novarini (VALUES, 2021)
Human resources are an important factor in an organization or company. Self efficacy is a belief in one's ability to perform tasks or actions needed to achieve certain things, while job motivation is a condition that creates encouragement, moves, activates and channels behavior so that it can work optimally. With the existence of self efficacy and high job motivation in the company, it is hoped that it can increase the job satisfaction of these employees. Job satisfaction is the perception felt by the individual whether it is pleasant or unpleasant for the individual to feel the work being done. This study aims to determine and analyze the effect of self efficacy and job motivation on job satisfaction of Pie Susu Chandra employees. Data collection was carried out by distributing questionnaires and carried out on 45 employees of Pie Susu Chandra. Data analysis in this study used SPSS version 17.0. The sample was determined by the population method or census method and the data testing techniques used included validity testing with a correlation coefficient (r)> 0,30, reliability testing with Cronbach Alpha. Classic assumption test and multiple linear regression analysis, to test and prove the research hypothesis. The results of this study indicate that the self efficacy variable has a positive and significant effect on job satisfaction as indicated by a significance value of 0,023. Job motivation variable has a positive and significant effect on job satisfaction as indicated by a significance value of 0,000.